Construction of the Public Service Platform for Gear Strength and Reliability Test Detection Technology - Meng Lingxian; Li Jiqiang; Zhang Zhihong; Wang Zhengbing (Jixie chuandong)
The background and necessity about the construction of the public service platform for gear strength and reliability test technology of strengthening foundation engineering project of the Ministry of Industry and Information Technology are briefly introduced. The function of eight sub- platforms are outlined. The key generic technology research and demonstration application progress are introduced. It has guiding significance for the design,manufacture,testing etc. of the gear production.